2018
DOI: 10.3847/1538-4357/aaafcd
|View full text |Cite|
|
Sign up to set email alerts
|

After the Fall: The Dust and Gas in E+A Post-starburst Galaxies

Abstract: The traditional picture of post-starburst galaxies as dust-and gas-poor merger remnants, rapidly transitioning to quiescence, has been recently challenged. Unexpected detections of a significant ISM in many post-starbursts raise important questions. Are they truly quiescent and, if so, what mechanisms inhibit further star formation? What processes dominate their ISM energetics? We present an infrared spectroscopic and photometric survey of 33 SDSS-selected E+A post-starbursts, aimed at resolving these question… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(114 citation statements)
references
References 164 publications
3
108
0
Order By: Relevance
“…As a result, 37 PSBs from French et al (2018a), 12 PSBs from Alatalo et al (2016a), and 11 PSBs from Rowlands et al (2015) have detections in 3 Herschel bands 2 , constituting our final sample of 58 PSBs in total 3 . The 37 PSBs from French et al (2018a) are labeled EAH01-EAH18 and EAS01-EAS15, consistent with the nomenclature in French et al (2015) and Smercina et al (2018), and F34-F37, for those without previous names. Their redshifts are 0.02 < z < 0.11.…”
Section: Sample Selectionsupporting
confidence: 62%
See 3 more Smart Citations
“…As a result, 37 PSBs from French et al (2018a), 12 PSBs from Alatalo et al (2016a), and 11 PSBs from Rowlands et al (2015) have detections in 3 Herschel bands 2 , constituting our final sample of 58 PSBs in total 3 . The 37 PSBs from French et al (2018a) are labeled EAH01-EAH18 and EAS01-EAS15, consistent with the nomenclature in French et al (2015) and Smercina et al (2018), and F34-F37, for those without previous names. Their redshifts are 0.02 < z < 0.11.…”
Section: Sample Selectionsupporting
confidence: 62%
“…As previous studies have shown that FIR (λ 40µm) photometry is crucial (da Cunha et al 2008;Dale et al 2012), we define our sample as those galaxies among the aforemen-tioned three samples of PSBs with archival FIR data. In addition to utilizing the processed WISE and Herschel data from Smercina et al (2018) for 33 PSBs from French et al (2015), we searched for Herschel observations of other galaxies in these three samples in the PACS Point Source Catalog ) and SPIRE Point Source Catalog (Schulz et al 2017), available at the NASA/IPAC Infrared Science Archive (IRSA) 1 . As a result, 37 PSBs from French et al (2018a), 12 PSBs from Alatalo et al (2016a), and 11 PSBs from Rowlands et al (2015) have detections in 3 Herschel bands 2 , constituting our final sample of 58 PSBs in total 3 .…”
Section: Sample Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…dependence on SFR. While the shapes of attenuation curves can vary (Kong et al 2004;Kriek & Conroy 2013;Salim et al 2018) and the dust property can be different in the burst component (Smercina et al 2018), exploring its effect on structures over the entire parameter space is beyond the scope of this paper. Instead, we show an illustrative case on how spatially non-uniform attenuation may affect the color and size.…”
Section: Effect Of Dust Attenuationmentioning
confidence: 99%